Field Enhancement in a Grounded Dielectric Slab by Using a Single Superstrate Layer. (31st October 2012) - Valagiannopoulos, Constantinos A.; Tsitsas, Nikolaos L.
Abstract : The addition of a dielectric layer on a slab configuration is frequently utilized in various electromagnetic devices in order to give them certain desired operational characteristics. In this work, we consider a grounded dielectric film-slab, which is externally excited by a normally-incident Gaussian beam. On top of the film-slab, we use an additional suitably selected single isotropic superstrate layer in order to increase the field concentration inside the slab and hence achieve optimal power transfer from the external source to the internal region. We define a quantity of interest, called "enhancement factor, " expressing the increase of the field concentration in the film-slab when the superstrate is present compared to the case that it is absent. It is shown that large enhancement factor values may be achieved by choosing properly the permittivity, the permeability, and the thickness of the superstrate. In particular, it is demonstrated that the field in the film-slab is significantly enhanced when the slab is composed by an ϵ -near-zero (ENZ) or low-index metamaterial.